1998
DOI: 10.1159/000028668
|View full text |Cite
|
Sign up to set email alerts
|

Complications after Selective Posterior Rhizotomy for Spasticity in Children with Cerebral Palsy

Abstract: Selective dorsal rhizotomy (SDR) has been shown to be an effective treatment for the spasticity of cerebral palsy, but few studies have addressed specifically the side effects of the procedure. A retrospective study was performed to determine the frequency and nature of complications in 158 children who had undergone SDR at British Columbia’s Children’s Hospital from 1987 to 1996. Intraoperative, preoperative (immediate postoperative until discharge at approximately 7 days) and postdischarge complications occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 32 publications
1
38
0
1
Order By: Relevance
“…Only minor and transitory complications, similar to those described in the literature [20, 21], were reported after surgery. Three cases (4.2%) of transient urinary retention requiring catheterization were documented.…”
Section: Resultssupporting
confidence: 65%
“…Only minor and transitory complications, similar to those described in the literature [20, 21], were reported after surgery. Three cases (4.2%) of transient urinary retention requiring catheterization were documented.…”
Section: Resultssupporting
confidence: 65%
“…In the Cape Town series with a 7-year follow-up, only 3 out of 51 patients had a clinically detectable decrease in sensation [26]. Persistent sensory loss of no clinical significance was noted in 3.8% of patients in another report [62]. Arens et al [26]noted increased weakness after selective posterior rhizotomy.…”
Section: Complications Of Rhizotomymentioning
confidence: 99%
“…Park [31]followed 690 patients and encountered no weakness, CSF leak, meningitis or neurogenic bladder, but noted a small number of patients with bronchospasm, pneumonia or urinary tract infection. Other series have reported persistent neurogenic bladder in 14.4% [63]and 1.3% of patients [62], respectively.…”
Section: Complications Of Rhizotomymentioning
confidence: 99%
“…Abbot et al 2 reported a higher complication rate with selective posterior rhizotomy, although most of the complications were transient (lower extremity dysesthesias) or related to anesthesia (bronchospasm). Asymptomatic but clinically detectable proprioceptive or cutaneous sensory losses occurred postoperatively in 3 of 51 patients in one series, 8 in 22 of 158 children in a recent series, 119 and in 7 of 30 patients in a series of older children and young adults. 101 Clinically significant residual spasticity limiting improvements in functional outcome may persist and is probably due to an insufficient percentage of rootlets being sectioned.…”
Section: Peripheral Proceduresmentioning
confidence: 85%